Top Indonesia’s Journal Efficiency Analysis: Bibliometrics (Scientific Strength) and Data Envelopment Analysis (DEA) - Ibrahim, Cecep (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
This study aims to analyze the efficiency of a journal by examining the correlation between the number of researchers associated with the journal and the expenses borne by researchers for publication concerning the scientific strengths achieved. The analysis is conducted through the Data Envelopment Analysis (DEA) approach. The data for scientific journal articles is collected from the metadata of Scopus, and WoS (Web of Science) was indexed in SINTA 1. Meanwhile, the APC (Article publication charge) data was obtained from the journal website. The input variables include the author, the editorial team, and the APC. In contrast, the output variables in this study are the scientific strength (publications and citations) generated. The study showed that the SINTA 1 journal indexed in Scopus and WoS with a DEA value of 1,000 was Operations and Supply Chain Management: An International Journal. The DEA value for journals indexed in Scopus and WoS is greater compared to the DEA value of journals indexed in WoS, as opposed to the DEA value of journals indexed in Scopus, but the difference is small.